Slava Ukraini [videorecording (DVD)] - Lévy, Bernard-Henri; Hertzog, Gilles (Cohen Media Group, Kino Lorber, 2023)
One year after the beginning of the war in Ukraine, philosopher Bernard-Henri Levy takes us to the heart of the conflict through a war diary made during the second half of 2022. From Kharkiv, in the Donbas, to Kherson, in the aftermath of the city's liberation, this documentary bears witness to the ravages of war through the testimonies of soldiers, chronicles of the front, and portraits of civilians, and shares with us the struggle of the Ukrainian people.